Giant Cell Tumor of Tendon Sheath - Benedict Djitro, Timotius; Harjanti, Dyonesia Ary; Suryawinata, Kidyarto; Karman, Iwan Irawan (Cermin Dunia Kedokteran, 2019)
Giant cell tumor of tendon sheath (GCTTS) adalah tumor kedua tersering di tangan, tetapi relatif jarang ditemui pada praktek sehari-hari. Tumor yang cenderung timbul pada wanita berusia 30-50 tahun ini tidak memiliki gejala spesifik sehingga sulit dibedakan dari tumor lain. Angka rekurensi tinggi sehingga sering muncul kembali setelah eksisi. Pemeriksaan histopatologi pre-operatif penting untuk diagnosis agar penanganan tepat untuk menekan rekurensi.Giant cell tumor of tendon sheath (GCTTS) is the 2nd most common tumor in the hand but is rarely encountered in everyday practice. The tumor has a tendency to develop in women aged 30-50 years and has no specific symptoms, making GCTTS difficult to be distinguished clinically from other tumors occurring mainly in the hand. High recurrence rate also made these tumors often reappear despite having been excised. Pre-operative histopathologic examination is important in diagnosis so appropriate steps can be taken to suppress the recurrence rate.Â